Factors associated with the development of skin allergies in premature newborns in the first year of life - Leonardo Bigolin Jantsch; Bruna Paola de Lima Bridi; Giovana Dornelles Callegaro Higashi; Andrea Moreira Arrué; Diúlia Calegari de Oliveira; Eliane Tatsch Neves
ABSTRACT Objective To identify the factors associated with the development of skin allergies in the first year of life in moderate and late preterm infants. Method: This is a cross-sectional study with 151 moderate and late preterm infants, born between May 2016 and May 2017. Participants were evaluated in the 3rd, 6th, 9th and 12th months of life, in telephone interviews. Statistical analyzes were performed in the SPSS software with frequency comparison tests and logistic regression. Results: The prevalence of skin allergy, in the perception of caregivers, among late and moderate preterm infants was 16%. Factors such as being admitted to neonatal intensive care (p = 0.006) and not being breastfed (p = 0.041) showed a significant association with the development of skin allergies in the 3rd and 12th months of life, respectively. Conclusion: Skin allergy, in the perception of caregivers, is more severe in newborn infants who have clinical respiratory and gastrointestinal manifestations, be it conditioning or cause-effect. Breastfeeding proved to be a protective factor in the first year of life.